The Phenomenon of Post Truth Political Campaigns on Facebook Social Media - Limbu, Lidya; Nastain, M; Mutiara, Mutiara (Indonesian Journal of Advanced Research, 2024)
Social media has become an electronic media for its users as a forum to express opinions and express ideas, so that it can present popular news, trending topics and can even be used by users to report fake news. Especially Facebook social media. Social media with different types of groups with positive comments and negative comments. Taking into account the many phenomena of fake news and post truth on social media, the researcher in this study studied political issues, more precisely during the campaign period. This study uses a qualitative descriptive method. The research method was carried out to obtain an overview of the application of the post truth phenomenon through Facebook social media as a media of information about post truth. The phenomenon of Post Truth in political campaigns on Facebook social media has a significant impact on the spread of false or inaccurate information, influence on voters' political opinions and attitudes, and voter participation in the political process. The spread of misinformation is a major challenge in political campaigns on Facebook. Fake news, false claims, and data manipulation often spread quickly and get more attention than honest content. The conclusion shows the need for coordinated action from various parties to address the Post Truth Phenomenon in political campaigns on Facebook social media. Facing the phenomenon of Post Truth in political campaigns on Facebook social media is a complex challenge, but coordinated measures and sustainable solutions will help maintain the integrity of democracy and social media.